Metode K-Means Untuk Pemetaan Persebaran Usaha Mikro Kecil Dan Menengah - Dwi Remawati; Dicky Jordan Aji Putra; Tri Irawati (STMIK Sinar Nusantara, 2021)
Developments in the current era of globalization are very dependent on the economic sector which is the benchmark of success carried out by the government. The role of the community in national development in the economic field is the existence of Micro, Small and Medium Enterprises (MSMEs). To increase the role of MSMEs as a benchmark for the success of the economic sector, there must be support from the government, such as assistance for business owners with limited costs. The purpose of this study is to determine community business groups as a measure of the level of business, making it easier for the government to provide assistance. The K-Means Clustering method is a method used for grouping business levels based on the income that exists in today's society. The result of this research is a website-based business-level grouping system used by the Cooperatives and SMEs Office by grouping them into micro, small and medium-sized businesses based on income/assets.